Limits of Soviet Power - Kolodziej, Edward A. author. aut Link
XX, 531 p.
Keywords: An evaluation of Soviet efforts to penetrate the major regions in the southern hemisphere, concluding that success has been modest and continues to be costly. It is suggested that a world society could emerge based on socio-economic and political competition rather than conflict and arms races.